The AppA and PpsR Proteins from Rhodobacter sphaeroides Can Establish a Redox-Dependent Signal Chain but Fail To Transmit Blue-Light Signals in Other Bacteria - Jäger, Andreas (American Society for Microbiology, 2007)
The AppA protein of Rhodobacter sphaeroides has the unique ability to sense and transmit redox and light signals. In response to decreasing oxygen tension, AppA antagonizes the transcriptional regulator PpsR, which represses the expression of photosynthesis genes, including the puc operon. This mechanism, which is based on direct protein-protein interaction, is prevented by blue-light absorption of the BLUF domain located in the N-terminal part of AppA. In order to test whether AppA and PpsR are sufficient to transmit redox and light signals, we expressed these proteins in three different bacterial species and monitored oxygen- and blue-light-dependent puc expression either directly or by using a luciferase-based reporter construct. The AppA/PpsR system could mediate redox-dependent gene expression in the alphaproteobacteria Rhodobacter capsulatus and Paracoccus denitrificans but not in the gammaproteobacterium Escherichia coli. Analysis of a prrA mutant strain of R. sphaeroides strongly suggests that light-dependent gene expression requires a balanced interplay of the AppA/PpsR system with the PrrA response regulator. Therefore, the AppA/PpsR system was unable to establish light signaling in other bacteria. Based on our data, we present a model for the interdependence of AppA/PpsR signaling and the PrrA transcriptional activator.